Social anatomy of economic growth - Pande, G.C. (New Delhi, 1990)
The book presents very fresh and vibrating data to establish the pro posed hypotheses on the vital roles of social determinants of economic growth. It offers a highly documented analysis of facts collected from field and pulpitating with life. The publica tion has been brought out to comme morate birth centenary year (April 14, 1990 to April 14, 1991) of the great jurist, statesman, social reformer and architect of Indian Constitution. Its central theme rotates round the policy-issues in priority-based social engineering specially the programm ing for amelioration in the state and status of lagging and socially as well as economically downtrodden strata of Indian society. The text-material exhibits interesting empirical evi dences from tradition based and poverty-ridden society. The approach, logic and filteration process of con clusions is scientific and methodical. The book analyses levels of cultural heritage, development of human and supporting resources, physical resource constraints, inter-group social inter-action, participatory flows in work, earnings, saving and invest ment propensities, challenge and response patterns, orientation for searching opportunities, aspirational dimensions etc. in the continued lively discussion. The discussion weaves with the thread-work of logic so as to make the clues more promi nent suggesting fundamental policy correctives. The material is highly revealing to inquisitive minds who seek to discover determinants of silent transition to the state of self propelled growth of, so far, vast vulnerable strata of population in chronic poverty ridden economies. The core part of this study covers analysis of animators of 'change' in attitudes, equipment and apparatus. ascending status and social recogni tion, will to achieve, ability to perform and other changing modes of sociospheric interaction.
Keywords: Economic development